Impacts of online advertising on business performance - Semerádová, Tereza, 1989-; Weinlich, Petr, 1976- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book examines online advertising activities and their connection to business performance in online environments. It also explores online communication channels including website presentation, social media, advertising platforms, and e-mailing"--